Novel findings from family-based exome sequencing for children with biliary atresia - Kien Trung Tran (Nature Portfolio, 2021)
Abstract Biliary atresia (BA) is a progressive inflammation and fibrosis of the biliary tree characterized by the obstruction of bile flow, which results in liver failure, scarring and cirrhosis. This study aimed to explore the elusive aetiology of BA by conducting whole exome sequencing for 41 children with BA and their parents (35 trios, including 1 family with 2 BA-diagnosed children and 5 child-mother cases). We exclusively identified and validated a total of 28 variants (17 X-linked, 6 de novo and 5 homozygous) in 25 candidate genes from our BA cohort. These variants were among the 10% most deleterious and had a low minor allele frequency against the employed databases: Kinh Vietnamese (KHV), GnomAD and 1000 Genome Project. Interestingly, AMER1, INVS and OCRL variants were found in unrelated probands and were first reported in a BA cohort. Liver specimens and blood samples showed identical variants, suggesting that somatic variants were unlikely to occur during morphogenesis. Consistent with earlier attempts, this study implicated genetic heterogeneity and non-Mendelian inheritance of BA.